Synthesis of Novel Thiazolidin‐4‐ones and Thiazinan‐4‐ones Analogous to Rosiglitazone. (28th November 2018) - das Neves, Adriana M.; Campos, José C.; Gouvêa, Daniela P.; Berwaldt, Gabriele A.; Goulart, Taís B.; Avila, Cinara T.; Machado, Pablo; Zimmer, Geórgia C.; Cunico, Wilson
Abstract : This work reports the synthesis of thiazolidin‐4‐ones and thiazinan‐4‐ones analogous to rosiglitazone, a potent antidiabetic drug. The desired compounds were synthesized with moderate to good yields by one‐pot reactions between different primary amines, mercaptoacetic or mercaptopropionic acids, and the 4‐(2‐(methyl(pyridin‐2‐yl)amino)ethoxy)benzaldehyde. The cyclocondensation reactions were carried out for 20 h, and all the products were characterized by 1 H and 13 C nuclear magnetic resonance spectroscopy, mass spectrometry, and one example by X‐ray diffraction. Abstract :